Pola Dakwah Tradisionalis Di Kampung Adat Cireundeu - Ahmad Aliadin; Acep Aripudin; Iwan Sopwandin; Anwar Shadikin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
AbstractThe success of a missionary in delivering da'wah cannot be separated from the effective pattern he uses. Tabligh or Da'wah is a moral force that is able to drive social change and offers an alternative in building the future dynamics of the ummah, by taking the right, creative and wise ways and strategies. This paper aims to describe the pattern of da'wah in the Cireundeu Cimahi Traditional Village. This research uses descriptive analysis method with a qualitative approach. Data collection techniques used are observation, interviews, and documentation studies. The results of this study explain that Ustad Abdullah uses a traditionalist pattern, namely conveying Islamic messages or teachings from the yellow book. Using the method of delivery by word of mouth, by action, and equipped with writings from books, magazines or relevant leaflets obtained from outside. Cultural communication used is low context communication.Several factors caused the development of da'wah in the Cirendeu village to be hampered, namely: 1) Ingrained customs; 2) lack of creativity of missionaries; 3) limitations of missionaries; 4) The method of da'wah is monotonous; 5) The negative mindset of the followers (adherents of Sunda Wiwitan) towards Muslims; 6) there is no motivation of religious figures.